Penilaian Praktik Sholat Jenazah Anggota Divisi Wanita Badan Kenaziran Masjid Al-Ikhwan - Ahmad Riadi Daulay (Journal on Education, 2023)
People frequently become forgetful during the funeral prayers, forgetting to read or even to make the necessary movements. This study intends to evaluate the women's section of the Naziran Agency of the Al-Ikhwan mosque's practice of offering funeral prayers (BKM). The Al-Ikhwan Dusun III Mosque, Bandar Setia Village, Percut Sei Tuan District, and Deli Serdang Regency were the sites of this study, which employed a qualitative methodology. 30 people served as study informants in all. using questionnaires, observation, and documentation studies, as well as interviews, to gather data. The study's findings revealed that: (1) standing up straight had very good results; (2) reading the recitation of the intention for the funeral prayer; (3) raising both hands during takbiratul ihram; (4) reading surah al-Fatihah; (5) reading sholawat; (6) reading the prayer Allahummaghfirlahu warhamu; (7) reading the Allahumma latahrimna; and (8) reading the pranic incantation all had very good results. As a result, it was determined that the women's division of the BKM Al-Ikhwan Mosque's performance of the burial prayer was very good.